Análisis de los estados financieros y la toma de decisiones en la Gerencia Sub Regional de Ucayali Contamana año 2022 - Panaifo Bardales, Nelly (2023)
The research established as an objective to determine the relationship between the analysis of the financial statements and decision making in the Sub Regional Management of Ucayali - Contamana year 2022. Which I opt for is an applied type study, descriptive level - correlational and design not experimental. In the investigation, the survey was used as a technique and the questionnaire as an instrument to collect important information. Concluding that, the analysis of the financial statements is qualified as regular (24%) since sometimes it prioritizes the provision of information to the people responsible for the economic activities of the company; Therefore, it always compares its homogeneous financial statements to determine the increases and decreases or variations of the accounts, from one period to another. For its part, decision-making is rated as regular by 27% because workers sometimes analyze the factors that impact the environment to make decisions, and sometimes prioritize the solution of the problem in terms of importance, urgency and time. time it requires. In conclusion, it was determined that there is a significant relationship between analysis of financial statements and decision making, which has been corroborated by a correlation coefficient of 0.725, which is at a considerable positive level, with a significance (bilateral) of 0.000.